THE STELAR ANATOMY OF STIPE AND ITS TAXONOMIC SIGNIFICANT IN DIPLAZIUM (ATHYRIACEAE) - Titien Ngatinem Praptosuwiryo; Dedy Darnaedi (Floribunda, 2014)
Anatomical study on transection of stipe near lamina were carried out on 27 species of Diplazium from Western part Malesia (Java, Sumatra, Kalimantan). The aim of this study is to examine stelar anatomical characters for supporting species delimitation in Diplazium. The leaf-trace shape of Diplazium stipe is varying among species and constant among the adult individuals in a species. Leaf-trace shapes of Diplazium can be classified into five main types: (1) uninterrupted V-shaped, (2) interrupted V-shaped, (3) uninterrupted U-shaped, (4) interrupted Ushaped, and (5) W-shaped. Each type diversifies into some different derivative forms that enable to determine a species among closely related species. Therefore the leaf-trace shapes are important diagnostic character which support species delimitation in Diplazium.